Mycoplasma genitalium: high prevalence of resistance to macrolides and frequent anorectal infection in men who have sex with men in western Sydney. (22nd March 2018) - Couldwell, Deborah L; Jalocon, Dean; Power, Melissa; Jeoffreys, Neisha J; Chen, Sharon C-A; Lewis, David A
Abstract : Objectives: We aimed to estimate the prevalence of Mycoplasma genitalium infection and of mutations linked to macrolide resistance using the ResistancePlus MG assay (SpeeDx, Sydney, New South Wales, Australia) in first-void urine (FVU), anorectal and oropharyngeal samples from men who have sex with men (MSM) attending Western Sydney Sexual Health Centre (WSSHC). Methods: Consecutive symptomatic and asymptomatic MSM attending for STI testing were prospectively enrolled. M. genitalium testing using the ResistancePlus MG assay was performed on FVU, anorectal and oropharyngeal samples routinely collected for Chlamydia trachomatis and Neisseria gonorrhoeae assays. Results: Overall, the prevalence of M. genitalium infection in the study group was 13.4% (68/508). Most (79.4%, 54/68) M. genitalium harboured macrolide resistance mutations (87.5% of urethral and 75.6% of anorectal infections). The anorectum was the most commonly infected site (45/505, 8.9%), followed by the urethra (24/508, 4.7%). No oropharyngeal M. genitalium infections were detected (0/508). Most of the anorectal (93.3%) and urethral (79.2%) infections were asymptomatic. MSM who were taking HIV pre-exposure prophylaxis (PrEP) were twice as likely to be infected with M. genitalium compared with MSM who were not on PrEP (OR 2.1, 95% CI 1.3 to 3.6; P=0.0041). Always using condoms for anal sex in the last 3 months was protective of infection (OR 0.8, 95% CI 0.6 to 1.0; P=0.0186). Conclusions: We demonstrated a high prevalence of M. genitalium and very high levels of macrolide resistance among MSM attending WSSHC. Our findings support the routine use of an assay to detect macrolide resistance mutations in M. genitalium infections. This will ensure, in regions or populations with high rates of macrolide resistance among M. genitalium strains, that first-line treatment with azithromycin will only be used if a macrolide-sensitive strain is identified.